Comparative analysis of microplastic release under real-use simulations in disposable polystyrene containers (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
Polystyrene is a potential carcinogen when ingested; however, the containers in which food is transported and consumed are made of polystyrene. The aim of this study was to evaluate and compare the release of microplastics (MPs) using two treatment conditions: during food transport and when food is consumed from the container, which involves mechanical damage caused by plastic utensils. Twenty new polystyrene containers were analysed (n = 10 per treatment). In the first group, the containers were washed and the water was filtered, whilst in the second group, gelatine was used to simulate solid food and cuts and pinching were applied for three minutes. The results showed average releases of 25.4 ± 9.3 MPs during transport and 72.7 ± 29.1 MPs during consumption, with significant differences (H = 15.42; p = 0.0015). Polystyrene releases MPs even without handling, and mechanical damage triples its emission, calling into question its safety for food use and its environmental sustainability.